EKSPLORASI BUDAYA MENGHIDUPKAN TARI DAERAH DALAM PERAYAAN KARTINI DI CIREBON - Magdalena, Lena; Febima, Mesi; Hatta, Muhammad (STKIP PGRI SITUBONDO, 2024)
The celebration of Kartini's Day in Cirebon offers a unique platform for junior and senior high school students to delve into and appreciate the richness of local culture. In this context, cultural exploration becomes crucial to revitalizing the essence of traditional dance as an integral part of the celebration. This dedication explores approaches that can be used to introduce and present regional dances as an essential component of the celebration. Focusing on the nuances of regional classical dance, this article discusses concrete efforts to involve students in understanding the values of bravery, beauty, and grace reflected in traditional dance movements. In the context of Kartini's Day festival, this cultural exploration serves as a form of celebration and a means to strengthen the local cultural identity and foster appreciation for invaluable cultural heritage. In conclusion, through this cultural exploration, it is hoped that the spirit of Kartini can continue to be revived, and cultural heritage can be preserved for future generations. Thus, this cultural exploration serves as a means to commemorate Kartini's contributions and as a platform to deepen understanding of local cultural heritage and foster creativity and appreciation for traditional arts. Amidst the tide of modernization, efforts like these are crucial to ensure that cultural values and traditions remain alive and relevant for the younger generation.